2020
DOI: 10.1001/jamadermatol.2019.4194
|View full text |Cite
|
Sign up to set email alerts
|

Dermatopathologists’ Experience With and Perceptions of Patient Online Access to Pathologic Test Result Reports

Abstract: IMPORTANCE Many patients presently have access to their pathologic test result reports via online patient portals, yet little is known about pathologists' perspective on this topic. OBJECTIVE To examine dermatopathologists' experience and perceptions of patient online access to pathology reports. DESIGN, SETTING, AND PARTICIPANTS A survey of 160 dermatopathologists currently practicing in the United States who are board certified and/or fellowship trained in dermatopathology was conducted between July 15, 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…As with all new technologies, changes in work practice can be more challenging to implement than the technology itself. In a recent survey, only a quarter of dermatopathologists reported that if their notes were accessible they would need specialized training in how to communicate with patients (14). Going further, we suggest that in the new era of open notes, it is imperative that all clinicians are trained in how to preserve the traditional functions of medical notes, and in maximizing the potential new benefits of this communication tool.…”
Section: Conclusion and Recommendationsmentioning
confidence: 84%
See 2 more Smart Citations
“…As with all new technologies, changes in work practice can be more challenging to implement than the technology itself. In a recent survey, only a quarter of dermatopathologists reported that if their notes were accessible they would need specialized training in how to communicate with patients (14). Going further, we suggest that in the new era of open notes, it is imperative that all clinicians are trained in how to preserve the traditional functions of medical notes, and in maximizing the potential new benefits of this communication tool.…”
Section: Conclusion and Recommendationsmentioning
confidence: 84%
“…How do healthcare clinicians view the practice? While the majority of surveyed physicians consider open notes to be a good idea (5) there does appear to be some variation in attitudes both between medical specialties (2,(11)(12)(13)(14) and countries (14,15). Mental health clinicians, for example, including psychiatrists, in the U.S. and in Sweden appear to be more cautious [(11, 12), p. 2].…”
Section: Patients' and Doctors' Experiences Of Open Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…The eligibility criteria were as follows: they were currently practicing in the United States, were board‐certified and/or fellowship‐trained in dermatopathology, had interpreted melanocytic skin biopsies within the previous year, and were expected to continue interpreting melanocytic skin lesions for the next 2 years. Eligible dermatopathologists were invited to enroll and to complete an online survey of demographic and clinical practice characteristics 19 between July 2018 and September 2019; it included the question “How often do you provide a synoptic report for melanoma cases?” with possible responses of “always,” “sometimes,” and “never.”…”
Section: Methodsmentioning
confidence: 99%
“…As a part of the study, participants completed an online survey as described previously. 18,19 The survey queried dermatopathologists about their demographics, training, experience, clinical practice, opinions on diverse terminology and adoption of the MPATH-Dx schema for reporting interpretations of melanocytic skin lesion cases. The survey questions pertaining to diverse terminology and adoption of the MPATH-Dx for classifying melanocytic skin lesions are available in Data S1.…”
Section: Methodsmentioning
confidence: 99%